Disease reaction of newly introduced Bt transgenic cotton hybrids in South-west region of Punjab - YADAV*, M.S. (Indian Phytopathology, 2008)
Six Bt cotton hybrids viz., RCH 134 Bt, RCH 317 Bt, MRC 6301 Bt, MRC 6304 Bt, Ankur 651 Bt and Ankur 2534 Bt were field evaluated against diseases during Kharif 2004 and 2005. All the Bt cotton hybrids were found significantly superior than non- Bt variety, F 846 (control) in reducing diseases like cotton leaf curl virus (CLCuV), bacterial blight (BB) and fungal foliar leaf spots (FFLS). However, the parawilt and Tirak incidence was noticed only in Bt hybrids. MRC 6304 Bt remained free from diseases. The disease indices of CLCuV (2.7%) on RCH 134 Bt and BB (2.4%) on RCH 317 Bt were significantly higher than others hybrids. Disease indices (0.2-2.8%) of FFLS were also recorded in Bt hybrids. The Parawilt incidences were maximum in Ankur 2534 Bt (2.6%) and Ankur 651 Bt (2.8%) during 2004 and 2005, respectively. Tirak has also shown occurrence (0.1-1.0% incidence) on Bt hybrids in the end of the season 2005.